The Role Online Counseling as a Part of Guidance and Counseling Services - Berru Amalianita; Ifdil Ifdil; Anggia Wahyu Agustin; Zikra Zikra (SCHOULID: Indonesian Journal of School Counseling, 2017)
Organizing online counseling is very helpful and possible to be developed in the world of guidance and counseling, especially in Indonesia. Although now specifically in Indonesia, there is no ethic that regulates but the existence of this media can support the implementation of guidance and counseling widely to improve the competence and efficiency of service for alleviating the problems faced by clients. Use and utilize information and communication technology.  The availability of formal institutions that will train these skills. And also specifically can be included in a special curriculum with regard to Information and communication Technology in guidance and counseling. And also hopefully in the future there will be the establishment of specialized counseling institutions that deal with specific issues online counseling and e-counseling services in general.